Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

What is solution of the differential equation:

\begin{aligned}x({yy'' + y'^2}) + yy' = 0\end{aligned}

What i am confused about it is the treatment of $$\left(\dfrac{dy}{dx}\right)^2$$ for solving this question. The given answer is \begin{aligned}ax^2 + by^2 = C\end{aligned}

share|cite|improve this question

A start: Let $u=yy'$. Then $x\frac{du}{dx}+u=0$.

I expect you can finish from here.

share|cite|improve this answer
Clever substitution. (+1) – user71352 Aug 9 '14 at 5:54
the solution comes out as\begin{aligned}u=\frac{c_1}{x}\end{aligned} \begin{aligned}\implies yy'=\frac{c_1}{x}\end{aligned} \begin{aligned}\implies ydy=\frac{c_1}{x}dx\end{aligned} on integrating further we get, \begin{aligned}\implies \frac{y^2}{2}=c_1lnx+C\end{aligned} how does it take the exact form of answer that is given? – Ritu Aug 9 '14 at 5:58
$\log|u| = -\log|x| + C \implies |u| = \frac{K}{|x|}$, not $K|x|$. – achille hui Aug 10 '14 at 1:10

Note that:

Given $$y^2$$

If we take the first derivative by implicit differentiation we get


Again taking a derivative we get

$$2(y')^2 + 2y''$$

This leads us to guess $u = y^2$ is a wise substitution.

From it the equation becomes

$$\frac{1}{2}(xu'') + \frac{1}{2}u' = 0$$

Now we divide out the 1/2 and make another substitution $u' = w$ to obtain:

$$xw' + w = 0$$

You can take it from here, once solved go backwards through the chain of substitutions

share|cite|improve this answer

I took a different approach and got the same answer as those given above. Since $$ x(yy''+y'^2)+yy'=0 $$is equivalent to $$ x\frac{d}{dx}(yy')=-yy' $$or $$ \frac{\frac{d}{dx}(yy')}{yy'}=-\frac{1}{x} $$then $$ \frac{d}{dx}ln(yy')=-\frac{1}{x} $$This integrates to give $$ ln(yy')=ln(x^{-1})+lnC_1 $$which simplifies to $$ yy'=\frac{C_1}{x} $$From here I used a Lie group $G(x,y)=(\lambda x,\lambda^\beta y), \lambda_o=1$ with stabilizers $\mu=\frac{y}{x^\beta}$ and $\nu=\frac{y'}{x^{\beta -1}}$ to rewrite the equation.
$$ \lambda^\beta y \lambda^{\beta -1} y'=\frac{C_1}{\lambda x} $$For the $\lambda$ terms to cancel out, $\beta =0$. Therefore, the first two nontrivial group stabilizers are $\mu=y$ and $\nu=xy'$. Rewriting the ODE in terms of its stabilizers, $$ \nu=\frac{C_1}{\mu} $$Since $$ x\frac{d\mu}{dx}=\nu=\frac{C_1}{\mu} $$we have $$ \frac{\mu ^2}{2}=C_1ln(x)+C_2 $$Allowing the constants to absorb the factor of two and remembering that $\mu=y$, $$ y=\sqrt{C_1ln(x)+C_2} $$There's nothing original about this solution, but I thought you might enjoy seeing an alternate approach to the problem itself. I picked up the Lie theory in Oak Ridge, and since so few people have ever seen it I like to share it when I can.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.